KEGIATAN PENANGKAPAN DAN PEMASARAN LOKAL KEPITING KELAPA (Birgus latro) DI PULAU YOI, MALUKU UTARA - Sulistiono Sulistiono; M. M. Kamal; Nurlisa A. Butet; Thomas Thomas Nugroho (Institut Pertanian Bogor, 2009)
This paper discussed about fishing and marketing activities on the coconut crab (Birgus latro) in Yoi Island. Field observation and interview with local fishermen was conducted from November 2007 to March 2008 in Yoi Island (North Maluku). The coconut crab is one of an important commodity for Yoi’s people. Fishing activities are done for 2-3 times per day, 5-7 days per week, and about 15 days per month. Catch results vary according to time (season) of the fish-ing activities (5-6 individual per day). The coconut crab weight was classified into 5 categories such as Big Tison (21 ons), Big (18-20 ons), Medium (14-17 ons), Small (11-13 ons) and Very Small (7-10 ons). Mostly, fishermen sell the catch to local collectors. Marketing of the coconut crab is in Yoi Island, Gebe Island, Ternate and Manado. Key words: coconut crab (Birgus latro), fishing activity, marketing, Yoi island of North Maluku